Historical Ecology, Archaeology and Biocultural Landscapes: Cross-Disciplinary Approaches to the Long Anthropocene - Bazan, Giuseppe; Castrorao Barba, Angelo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book collects a series of interdisciplinary contributions about Historical Ecology, Archeology and Biocultural Landscapes focused on the analysis of landscape dynamics during the Long Anthropocene. Through case studies across Europe, the Mediterranean, Asia and America, the volume offers a series of examples of approaches and applications to combine and stimulate an interdisciplinary debate between Natural Science and Humanities for understanding long-term human-environment interaction and historical sustainability.